Behavior in a Changing Landscape: Using Movement Ecology to Inform the Conservation of Pond-Breeding Amphibians - Joly, Pierre (Frontiers in Ecology and Evolution, 2019)
Movement, both within an individual’s home range and at the scale of dispersal, is a fundamental aspect of an animal’s life. The field of movement ecology has established a conceptual framework to analyze the lifetime movement of an organism, offering a sound basis for conservation actions since the movement range of many species has been altered by habitat fragmentation and degradation. An organism’s lifetime movement is organized around three main functions – exploitation, exploration, and relocation – which are associated with specific behavioral mechanisms and spatio-temporal scales. The movement ecology framework is a valuable tool as applied to amphibians, as managing these spatially structured populations requires in-depth knowledge of the behavioral mechanisms that determine movement. In terms of exploitation, these animals have a complex lifecycle, which involves migrating between different types of habitat, thus requiring them to cross a landscape matrix that may be more or less inhospitable. In terms of exploration and relocation, between-pond movements within the pond archipelagoes of a given population are frequent and strongly contribute to population resilience. Relocation also occurs at a larger scale, through long-distance dispersal to colonize new patches, exposing the individuals to unknown environments. Each function, at each scale, involves specific interactions between individual motivation (phenotype dependence) and environmental quality (context dependence) that determine decision-making and fitness outputs. Long-term exposure to local selective pressures can lead to differentiation in coping types that could be considered as Evolutionarily Significant Units (ESUs) for conservation. At the scale of a patch, the optimal direction of migration can be inherited, thus allowing the optimization of migration routes for juveniles. At the regional scale, a dispersal syndrome resulting in a greater propensity for boldness and exploration could be a response to unpredictable breeding sites or the high benefits of colonizing a rich habitat. Greater knowledge about such behavioral adaptations to specific situations would allow more targeted development of conservation measures or help to stop the spread of invasive species. The evolutionary context of movement behavior is thus of primary interest in designing effective conservation actions in a changing world.